Association of altitude with all-cause and cardiovascular mortality among patients with hypertension: a cohort study in Southwest China - Yu Xia; Linhong Pang; MingJing Tang; Zhiling Luo; Min Ma; Huadan Wang; Liping He; Lin Duo; Da Zhu; Xiangbin Pan (BMC Public Health)
Abstract Background Available evidence falls short in assessing the risk of long-term outcomes among individuals with hypertension residing at various altitudes. We aimed to investigate the association between residential altitude and the risk of all-cause and cardiovascular disease (CVD) mortality among hypertensive patients. Methods This cohort study encompassed 67,275 hypertensive patients aged ≥35 years who participated in China’s Basic Public Health Service Program in 2018. Participants were categorized into four groups based on their residence altitude: <500 m, 500-1,499 m, 1,500-2,500 m, and > 2,500 m. The associations between residential altitude and the risks of all-cause and CVD mortality were analyzed using Cox proportional hazards regression models. The dose-response relationship was performed by the restricted cubic spline with multivariable adjusted models. Results Among the 67,275 hypertensive patients included in the study (mean age of 63.9 years, with 45.3% male), 8,768 deaths were recorded, of which 5,666 were attributed to CVD. Following multivariate adjustment, when compared to the group residing at altitudes < 500 m, the groups living at altitudes of 500-1,499 m, 1500-2,500 m, and > 2,500 m exhibited significantly risks of all-cause mortality [HR = 1.45 (95% CI: 1.36–1.54), 1.35 (95% CI: 1.28–1.43), and 1.41 (95% CI: 1.28–1.54), respectively] and CVD mortality [HR = 1.47 (95% CI: 1.35–1.58), 1.42 (95% CI: 1.33–1.52), and 1.46 (95% CI: 1.31–1.62), respectively]. The restricted cubic spline curves revealed a nonlinear relationship between residential altitude and all-cause and CVD mortality. The risk of mortality was higher among participants with poorly controlled blood pressure, aged 65 years and above, and living in rural areas. Conclusions This study demonstrated a significant association between long-term residential high-altitude exposure and increased risks of all-cause and CVD mortality among hypertension patients. The implications of the findings call for a prioritization of public health resource allocation and early intervention efforts, especially for those living at high altitudes and in low-income areas where hypertension is prevalent.